Ostend through the Eyes of British Writers (1830-50): A Seaside Resort Abroad as a Home for the British Genteel Poor - Francois, Pieter (Hungarian Journal of English and American Studies, 2021)
This article analyzes how the British writers Frances Trollope (1779–1863) and William Makepeace Thackeray (1811–1863) described the Belgian coastal resort Ostend in the 1830s and 1840s. A special focus is placed on both the British travelers passing through Ostend and the British resident communities at Ostend. The article will highlight how the assessments of Frances Trollope and William Makepeace Thackeray of Ostend as a coastal resort frequented by the British can be unpacked fruitfully within two overarching themes: the theme of “genteel poverty” and “respectability” on the one hand, and the theme of “national identity” and “religious identity” on the other. These assessments by Frances Trollope and William Makepeace Thackeray are contextualized against the background of contemporary British guidebooks and travel accounts on Ostend, and against some statistics on the British traveller and resident communities in mid-nineteenth century Belgium. (PF)